The suspect. [Series 1] [videorecording (DVD)] - Berry, Peter (Screenwriter); Turner, Aidan, 1983-; Parkes, Shaun; James, Adam; Clifford, Sian; Robotham, Michael, 1960- (Sundance Now, 2023)
Joe O'Loughlin is a successful psychologist with a loving family, but a recent medical diagnosis has thrown his life off balance. When the police ask him to assist in the case of a murdered young woman, ghosts from his past begin to resurface.